2005
DOI: 10.1128/jb.187.19.6733-6741.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of TolB with the Translocation Domain of Colicin E9 Require an Extended TolB Box

Abstract: The mechanism by which enzymatic E colicins such as colicin E3 (ColE3) and ColE9 cross the outer membrane, periplasm, and cytoplasmic membrane to reach the cytoplasm and thus kill Escherichia coli cells is unique in prokaryotic biology but is poorly understood. This requires an interaction between TolB in the periplasm and three essential residues, D35, S37, and W39, of a pentapeptide sequence called the TolB box located in the N-terminal translocation domain of the enzymatic E colicins. Here we used site-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The results of previous ColE9 T-domain mutagenesis data can now be rationalized in the context of the TolB-ColE9 T pep32-47 complex structure (21)(22)(23). Mutations fall into two categories, those that abolish binding and those that result in weak binding to TolB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous ColE9 T-domain mutagenesis data can now be rationalized in the context of the TolB-ColE9 T pep32-47 complex structure (21)(22)(23). Mutations fall into two categories, those that abolish binding and those that result in weak binding to TolB.…”
Section: Resultsmentioning
confidence: 99%
“…A ''TolB box'' ( 35 DGSGW 39 ) has previously been described that is part of the natively unfolded T-domain where mutations (of non-glycine residues) abolish colicin toxicity (21,22). More recently, the potential TolB binding site has been extended by mutagenesis and NMR experiments (17,23), but it is still not clear whether the site is a contiguous or discontiguous epitope or whether regions outside the natively disordered domain are involved. Two complementary approaches were taken to delineate precisely the binding site in ColE9.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domains of co-licins have been postulated to be poorly structured regions based on the low amount of ordered secondary structures observed by circular dichroism, a weak dispersion of NMR signals, the absence of detection of corresponding electron density during X-ray crystallography studies, and high susceptibility to proteolytic degradation (6,125,132,147,496,546,607,650). Biophysical studies have demonstrated that the TolB binding sequence of colicin E9 becomes more structured when in interaction with TolB (125,248,431,632). Similarly, transition of the N-terminal domain of colicin N from a disordered state to a folded conformation is induced upon TolA C-terminal binding (5,6).…”
Section: Tol-dependent Colicinsmentioning
confidence: 99%
“…Overall, these data suggest that the N-terminal segments of the group A colicin translocation domains are disordered in their native states and fold into an ordered structure when binding a Tol subunit. This recognition mechanism has been suggested to contribute to the specificity of the recognition event, to allow a protein to bind several target partners, and to provide large protein binding surfaces in relatively small regions (168,241,248,362). Hierarchy of contacts during transit.…”
Section: Tol-dependent Colicinsmentioning
confidence: 99%
“…However, the details of colicin entry through OmpF are largely unknown. The cytotoxicity of colicin E3 is dependent on the interaction of the periplasmic TolB protein with the TolB box spanning residues 34 to 46 (18,19), which is contained in the 83-residue N-terminal translocation subdomain-the T83 segment. It is likely that the high Gly content of this subdomain and its resulting flexibility (11,41) allow it to traverse the outer membrane through a translocation complex that contains OmpF (25,47) and to interact with the TolB protein in the periplasmic space (6).…”
mentioning
confidence: 99%